Metódos não farmacológicos para alívio da dor e risco de cesárea: um estudo coorte retrospectivo - Rodrigues, Vanessa Aparecida Domingos da Silva (2019)
Introduction: The high prevalence of caesarean sections is a difficult global public health problem with which several maternal and neonatal complications have been associated. A wide range of interventions to reduce the high rate of caesarean sections is described in the literature. Among them, non-pharmacological labour pain management methods seem to be an interesting strategy for this purpose. Despite evidence on the benefits of these methods, few studies analysed the association of these methods with maternal and neonatal complications. Objective: To analyse the impact of non-pharmacological labour pain management methods on delivery mode and maternal/neonatal complications among women admitted for labour at the Federal University of Uberlandia hospital (HCU-UFU). Methods: Retrospective cohort comprising medical records from all women who had spontaneous labour or were submitted to induction or augmentation of labour at the University Hospital of the Federal University of Uberlandia (HCU-UFU) between January 1, 2013 and December 31, 2017. Medical records were selected based on the following International Classification of Disease (ICD-10) codes: 080, 081, 084.0, O84.1 or O84.2. We used descriptive analysis to characterize the study population and adjusted logistic regression to compare maternal sociodemographic and obstetric characteristics according to delivery mode and presence of maternal and/or neonatal complications. Multiple imputation was used to handle missing data. To assess the effects of non-pharmacological labour pain management methods and to correlate them to the study outcomes, we estimated the RR using unadjusted ratios in logistic regression models and adjusted ratios for maternal sociodemographic and obstetric characteristics. Results: We analysed 5,293 medical records of women who had spontaneous delivery or were submitted to induction or augmentation of labour. Of these, 37.9% had the use of a non-pharmacological labour pain management method registered: 1,582 (78.9%) women took warm shower baths, 1,281 (63.9%) used the Swiss ball, 352 (17.5%) tried different positions, 175 (8.7%) received relaxing massages, and 97 (4.8%) received guidance on appropriate breathing techniques. From the total of medical records analysed, 2,196 (41.5%) referred to caesarean sections and 448 (8.5%) had some maternal and/or neonatal complication registered. The use of non-pharmacological methods reduced the risk of caesarean sections in approximately 73% (RR 0.27; 95% CI 0.24 - 0.31), but did not have a detectable impact on the occurrence of maternal and neonatal complications (RR 0.89; 95% CI 0.71 - 1.13). Conclusion: Despite its low prevalence, the use of nonpharmacological labour pain management methods proved to be a significant factor to decrease the risk caesarean section. This is an important finding, especially in scenarios with high rates of caesarean sections like ours. Although this practice did not have an impact on the occurrence of maternal and neonatal complications, strategies to encourage the use of these methods should be encouraged to reduce the occurrence of unnecessary caesarean sections. Further studies to identify the efficacy of each method may help health professionals to offer more appropriate methods at different stages of labour.